1995
DOI: 10.1007/bf00191345
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical distribution of chromogranins A and B and secretogranin II in neuroendocrine tumours of the gastrointestinal tract

Abstract: The aim of the present study was to investigate immunohistochemically the distribution of chromogranin A, chromogranin B, and secretogranin II in a series of 152 neuroendocrine tumours of the gastrointestinal tract. Tumour tissues from 25 argyrophil gastric carcinoids, 18 gastrin and 5 somatostatin-producing tumours, 4 'gangliocytic paragangliomas', 49 classical argentaffin and 2 L cell appendiceal carcinoids, 27 classical ileal carcinoids, 17 rectal carcinoids, and 5 poorly differentiated neuroendocrine tumou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(37 citation statements)
references
References 33 publications
0
35
1
Order By: Relevance
“…The reason for the chromogranin A negativity in these tumors is not known. Interestingly, a similar lack of chromogranin A positivity is also seen in rectal NETs (Fahrenkamp et al 1995).…”
Section: Discussionmentioning
confidence: 61%
“…The reason for the chromogranin A negativity in these tumors is not known. Interestingly, a similar lack of chromogranin A positivity is also seen in rectal NETs (Fahrenkamp et al 1995).…”
Section: Discussionmentioning
confidence: 61%
“…Exceptions are ECLomas and parathyroid adenomas where CgB244-255 was not demonstrated. These tumor types also lacked immunoreactivity in reports by other authors using other CgB epitopes (Weiler et al 1988;Bordi et al 1991;Fahrenkamp et al 1995), but contain CgA epitopes Sonnleitner-Wittauer et al 1996).…”
Section: Chromogranin Bmentioning
confidence: 64%
“…Fahrenkamp et al (23) investigated 152 neuroendocrine tumors of the gastrointestinal tract using monoclonal antibody against human CgA, CgB (amino acids 306 -326), and CgC. They revealed that CgA is the major granin expressed in gastric carcinoids and in serotonin-producing carcinoids of the appendix and ileum.…”
Section: Discussionmentioning
confidence: 99%